الترادف ودوره في اللغة العربية - Munir, Muhammad Mubasysyir (UIN Maulana Malik Ibrahim Malang, 2020)
A synonym is a linguistic phenomenon that expands the horizons of expression and communication, and helps the speaker to open up broad creative horizons. There has been a lot of talk and discussion between scientists, linguists, writers and researchers, old and new. Many of them have counted it as a feature of Arabic, a feature of its features, and a manifestation of genius in it.This research mentioned the three divisions of the position of ancient linguists on synonym: supported its existence but was not complete, supported its the existence at all, and denied it. He also mentioned the opinions of modern scientists that divided synonym into complete synonymy and near synonymy. Then he mentioned the most prominent scientists of synonym and sealed his turn in Arabic. In summary, old scientists take the meaning of general synonym without any condition in order to expand the circle of it’s in the language. The modernists reversed them, narrowing the tandem circle by setting conditions on the occurrence of synonym.